Sikap Konsumen dan Kinerja Atribut Produk Mobile Banking (Studi Pengguna Mobile Banking di Kota Surabaya) - Andry Herawati; Sarwani; Indrarini DG (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
Mobile Banking is a form of banking information system service, which may be the best solution for busy customers. Regarding the number of customer complaints related to mobile banking applications, it is important to conduct this research to analyze which attributes influence customer attitudes towards the use of mobile banking services, and how the performance of banking attributes mobile. The research method used is a quantitative descriptive approach. The sampling technique used is simple random sampling, obtained from 100 respondents using mobile banking services. The data analysis method uses Fishbein's multi-attribute model and importance-performance analysis (IPA). The results of the study show that consumer attitudes towards the attributes of mobile banking are positive, with a value of 218.81. The performance of Mobile Banking attributes is analyzed by the Importance Performance Analysis, showing the results that the attributes that need to be prioritized to improve their performance are the attributes that are included in quadrant I (Main Priority): Mobile Banking website and ease of operation of Mobile Banking during transactions.